The Global Incidence, Mortality, and Burden of Breast Cancer in 2019: Correlation With Smoking, Drinking, and Drug Use - Allahqoli, Leila; Mazidimoradi, Afrooz; Momenimovahed, Zohre; Rahmani, Azam; Hakimi, Sevil; Tiznobaik, Azita; Gharacheh, Maryam; Salehiniya, Hamid; Babaey, Farah; Alkatout, Ibrahim (Frontiers in Oncology, 2022)
Aim: This study aimed to update the incidence, mortality, and burden of breast cancer using the Global Burden of Disease 2019 study. Materials: The incidence, mortality, and burden of breast cancer in 2019 were retrieved from Global Health Data Exchange (GHDx) database for all countries in the world for 2019, as this is the calendar year where the most updated incidence and mortality figures could be retrieved. Age-standardized rate (ASR) incidence, deaths, lost years of life, years of life with disabilities (YLDs), and adjusted years of life with disabilities (DALYs) of breast cancer in women were extracted from the online Global Burden of Disease data. In this study, data were extracted globally for 204 countries and groups based on SID index, WHO regions, continents, World Bank regions and 22 GBD regions. Results: The ASR of incidence of breast cancer was positively correlated with levels of the socio-demographic index. According to SDI, World Bank classification, and GBD the highest incidence of breast cancer was reported in countries with higher socioeconomic status, and in less developed countries, the incidence was lower. Based on the WHO regions, the highest incidence of breast cancer was reported in the EURO continent. The mortality rates of breast cancer among women in countries with low SDI, low-income economies, and Africa regions were even higher than the rates among women in high-income economies countries, despite the substantially lower incidence rates. According to WHO regions, the highest mortality ASR was in the EMRO Region, followed by AFRO. This study shows the highest ASR YLLs was related to the regions with low SDI economies.In different continents and World Bank High-Income classification, the highest ASR per 100 000 population of DALYs and YLDs were for Europe, followed by the United States and the lowest was in Africa. Conclusion:This GBD-based 2019 study provides comprehensive views of the incidence, mortality, and burden of breast cancer. Its incidence is more in regions higher socioeconomic status, and mortality and DALYs are higher in regions with low level of development. Therefore, better plans for screening and early detection programs in these countries are suggested.